Training needs of traditional marine fishermen in Kerala - Balasubramaniam, S., Kaul, P.N., Thiagarajan, R. and (Fishery Technology, 2021)
Training needs of 80 fishermen in 25 subject areas revealed a mean training need score of 23.0l; 95% wanted to get trained. The training needs were fairly strong in all subject areas, with the highest demand being for fishery engineering. Training need was also high for areas related to fishery technology. Most of the fishermen preferred to have the training at their own village, and in the months of June or July for an average period of 20.85 days. Education and income were positively related to intensity of training needs whereas age, number of family members, number of employed family members and experience in fishing were negatively correlated with it. These six variables explained 27 of the variance in training need intensity.